CAPACIDADE DE ABSORCAO DE AGUA, OLEO E FORMACAO DE ESPUMA DA FARINHA E CONCENTRADO PROTEICO DE FEIJAO-GUANDU (CAJANUS FLAVUS DC.) - Batistuti, José Paschoal [UNESP]; De Freitas, S. D. [UNESP] (My University, 1995)
Pigeonpea protein concentrate was prepared from full-fat decorticated raw flour. The water holding capacity of pigeonpea flour of decorticated seeds is 75% and its oil absorption capacity a 30%. The water holding capacity of the protein concentrate is three times the dry weight. The oil absorption capacity of the concentrate was 1,29 mL oil/g protein. The whipping capacity of the pigeonpea flour and its protein concentrate were evaluated.
Water and oil absorption capacity and whipping capacity of pigeonpea flour and protein concentrate
Keywords: Cajanus flavus DC.; isolate protein; oil absorption; pigeonpea; protein concentrate; water hydration capacity; whipping capacity; cajanus flavus extract; plant extract; protein; unclassified drug; flour; nonhuman; water absorption